2004
DOI: 10.1023/b:qure.0000031337.73269.64
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Quality of Life and Psychiatric Impairment for a Taiwanese Community Post-Earthquake

Abstract: This purpose of this study was to investigate the relationship between quality of life and psychiatric impairment in a Taiwanese community located near the epicenter of the 1999 earthquake, as assessed four to six months after the natural catastrophe. Trained assistants interviewed the 4223 respondents using the disaster-related psychological screening test (DRPST), an instrument specifically designed and validated by senior psychiatrists for assessment of psychiatric impairment after natural catastrophe. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
89
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 19 publications
13
89
4
Order By: Relevance
“…Similar results regarding demographic variables have been reported in a number of studies on victims of disasters e.g. [11][12][13]30], and also in other causes of trauma (e.g. in post-conflict displaced populations, [31]).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Similar results regarding demographic variables have been reported in a number of studies on victims of disasters e.g. [11][12][13]30], and also in other causes of trauma (e.g. in post-conflict displaced populations, [31]).…”
Section: Discussionsupporting
confidence: 71%
“…They reported that one year after the earthquake elderly people had a lower quality of life in domains related to physical health, psychological well-being, and environment compared to baseline pre-disaster assessments. Similar results for earthquake disasters were reported by [11,12] and for floods by [13]. In addition, others [14] have reported that high levels of negative post-disaster adjustment were associated with personal injuries, resource loss, and increased psychopathological symptoms.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The concept of HRQoL, focusing on functioning, has become increasingly popular in clinical and community samples as a valuable measure of overall subjective health in terms of biopsychosocial well-being and limitations. Nevertheless, only a few studies have addressed HRQoL after disastrous events; these demonstrated impaired HRQoL after various types of disasters [13][14][15][16][17][18], and after the September 11th terrorist attack [19].…”
Section: Introductionmentioning
confidence: 99%
“…Ceyhan, E. & Ceyhan, A., 2007;Choul et al, 2004;Tsai et al, 2007PTSD Germain et al, 2006Lensi et al, 1996Reed & Wittchen, 1998Bezerra De Menezes et al, 2008 Roberson-Nay et al, Turk et al, 1998 Bezerra Weisenbach et al, 2012Cahill et al, 2001Cahill et al, 2004;Canli et al, 2002Derntl et al, 2009Dickie & Armony, 2008Ohrmann et al, 2010PTSD Felmingham et al 2010 PTSD …”
mentioning
confidence: 99%